(untitled) (ELang | An English Language Education Journal, 2021)
The research paper is entitled ”The Effectiveness of Communicative Game Sequencing Pictures and Stories Game In Teaching Listening” which was written to be submitted to English Education Study Program of FKIP of UNIBBA as apartial fulfillment of requirements for taking Sarjana Pendidikan Degree the aim of the research is to find out whether or not of communicative game sequencing pictures and stories game in improving listening skill of second grade students at SMP Budi Mulya is effective and responses of the students when they learn English Listening through sequencing pictures and stories game. The research was classified as pre-experimental research. The main subjects of this research were 25 students of class VII at SMP Budi Mulya. The approach of the study was quantitative. Listening test were used as the instruments of eliciting the data. The action implemented in this research were using sequencing pictures and stories game, giving more explaination in English, making use of the pictures. The results of the research showed that the use of sequencing pictures and stories game in the English teaching and learning process was effective to improve the students listening skills there was an increase in the means scores 1,652 in the pre-test to 6,348 in the post-test. The increase of the means from pre-test to post-test was significant, it is proved by the t-test result that t-observed was higher than table (10,07>2,064). There were some good improvements in some aspects such as their familiarity in listening to English word. Moreover, commounicative game sequencing pictures and stories game successfully caught the students attention.